1959
DOI: 10.1172/jci103937
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Osmotic Behavior of the Human Erythrocyte*†

Abstract: Despite many previous studies of the osmotic properties of erythrocytes, unequivocal answers have not been given to two important questions: 1) Is the erythrocyte in osmotic equilibrium with its normal surrounding fluid? 2) When the osmotic properties of the surrounding fluid are varied, does the erythrocyte gain or lose water to the extent necessary to remain in osmotic equilibrium with the new surroundings-that is, does the erythrocyte behave as a perfect osmometer over a wide range?Previous work related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1962
1962
1985
1985

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Again, it is possible that the heating, like diamide treatment, dissociates the spectrinactin network from the rest of the membrane. The finding that if isolated spectrin in vitro is incubated at temperatures above 40°C it will no longer bind to the ghost membrane (Williams et al, 1959) also appears to support this possibility.…”
Section: Discussionmentioning
confidence: 89%
“…Again, it is possible that the heating, like diamide treatment, dissociates the spectrinactin network from the rest of the membrane. The finding that if isolated spectrin in vitro is incubated at temperatures above 40°C it will no longer bind to the ghost membrane (Williams et al, 1959) also appears to support this possibility.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have demonstrated the relationship between altered osmotic fragility and abnormal geometry of erythrocytes [1,11,21]. Elevated osmotic fragility, however, is not only important with respect to a long life-span of erythrocyte carriers and the encapsulated drugs, but also with respect to an uncontrolled breakdown of loaded cells in vitro and a reduced shelf-life.…”
Section: Discussionmentioning
confidence: 99%
“…As Soderstrom outlined his theory rather briefly, it will be considered in more detail here. The normal red cell can attain osmotic equilibrium with its environment over a fairly wide concentration range (Williams et al 1959). In this case the rapid water exchange (Sidel and Solomon 1957) quickly reduces any solute gradient which might act as a driving force for net solute movements.…”
Section: Mechanism Of Posthypertonic Hemolysismentioning
confidence: 99%